“Kepala Putik” on Women: Perspectives and Challenges in Balancing the Dual Role as Mother and Worker in Indonesia - Primadona, Fitry; Lenggogeni, Sari (Sawwa: Jurnal Studi Gender, 2024)
The dual roles carried out by Indonesian women as both mothers and workers have increasingly garnered attention amidst dynamic social and economic changes. This article explores the concept of "Kepala Putik" as a perspective accompanied by the stigma faced by Indonesian women in fulfilling these dual roles. The research utilizes a qualitative method with a literature study approach. The primary data sources stem from a comprehensive review of relevant literature, including scholarly articles, books, and reports related to the dual roles of women in Indonesia. This study highlights the increasing participation of women in the workforce in Indonesia, focusing on a literature analysis to understand the social perspectives and challenges faced by women in balancing these dual roles. The uniqueness of this research lies in its emphasis on the specific concept of "Kepala Putik" and how this stigma uniquely affects Indonesian women. The findings of this study reveal the complexity of stereotypes and social norms related to women who choose to work while continuing to fulfil their roles as mothers.